Contribution of Professor Alicja Jaruga to the development of accounting research directions - Przemysław Kabalski; Joanna Szwajcar (Zeszyty Teoretyczne Rachunkowości)
This article presents the work of Professor Alicja Jaruga in the field of financial reporting. Her contribu-tion to the development of this discipline is immense, both in terms of the number and diversity of topics investigated and the significance of the achievements in these areas of research. The issues explored by Professor Jaruga include the conceptual framework of financial reporting, socio-economic determinants of reporting models, legal and institutional context of financial reporting, intellectual capital and social responsibility reporting, valuation concepts (also in inflationary environments) and a broad range of other topics, both general and specific. Professor Jaruga’s definitions, ideas and conclusions form part of the canon of Polish accounting thought, and her research provides a model and inspiration for future genera-tions of researchers exploring issues in financial reporting.